2014
DOI: 10.1371/journal.pone.0099940
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling to Discover Putative Genes Associated with Paraquat Resistance in Goosegrass (Eleusine indica L.)

Abstract: BackgroundGoosegrass (Eleusine indica L.), a serious annual weed in the world, has evolved resistance to several herbicides including paraquat, a non-selective herbicide. The mechanism of paraquat resistance in weeds is only partially understood. To further study the molecular mechanism underlying paraquat resistance in goosegrass, we performed transcriptome analysis of susceptible and resistant biotypes of goosegrass with or without paraquat treatment.ResultsThe RNA-seq libraries generated 194,716,560 valid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 51 publications
3
82
0
Order By: Relevance
“…With one exception ( Echinochloa crus‐galli ), transcriptome analyses of HR to date have been conducted on diploid, allogamous species, such as Eleusine indica L., L. rigidum and A. myosuroides . As such, they reflect the relatively rapid evolution of HR in species with high levels of standing genetic variation, the ability to rapidly spread and create large populations and quickly fix advantageous alleles .…”
Section: Discussionmentioning
confidence: 99%
“…With one exception ( Echinochloa crus‐galli ), transcriptome analyses of HR to date have been conducted on diploid, allogamous species, such as Eleusine indica L., L. rigidum and A. myosuroides . As such, they reflect the relatively rapid evolution of HR in species with high levels of standing genetic variation, the ability to rapidly spread and create large populations and quickly fix advantageous alleles .…”
Section: Discussionmentioning
confidence: 99%
“…A general review of the literature (Tables and S1) reveals a wide array of RNA‐seq experimental set‐ups employed by weed researchers over the last few years . These initial set‐up decisions can drastically influence the number of transcripts that appear as significantly differentially expressed by the end of the analysis.…”
Section: Lessons From the Literaturementioning
confidence: 99%
“…In fact, one of these studies compared only one pooled HR sample with one pooled HS sample and produced 1310 DETs . Other studies with a single replicate returned much longer DET lists, with an average of 44 000 DETs returned in those papers . Controlling for the genetic background was done through either recurrent selection of a single population or by studying a segregating F 2 population …”
Section: Lessons From the Literaturementioning
confidence: 99%
“…; An et al . ). After paraquat spraying, the decrease of chlorophyll fluorescence (Fv/Fm) in S biotype was irreversible, whereas it was transient in the R biotypes, which recovered gradually afterward.…”
mentioning
confidence: 97%
“…Our previous study (An et al . ) indicated that the genes related to PAs could play a vital role in the paraquat resistance of E. indica . Salinity is one of the most severe environmental stresses that affect plant growth and limit crop productivity.…”
mentioning
confidence: 99%